TAKING PHILOSOPHICAL GROUNDS OF CORPORATE SOCIAL RESPONSIBILITY DEBATE SERIOUSLY - Mir Mohammadi, Seyed Mohammad Hossein (Bulletin of Taras Shevchenko National University of Kyiv. Philosophy, 2021)
Corporate Social Responsibility (CSR) is an important sphere in applied ethics. Different CSR theories have been presented during decades. Some of them are compatible with each other while some others are not. By focusing merely on the contents, it seems impossible to evaluate the different theories or to explain why different CSR theories and programs have been presented. However, this paper suggests that the variety of the debate comes from the (philosophical) grounds these theories are based. These grounds, as roots of CSR theories, can well explain, classify and evaluate different types of CSR theories. As a result of the philosophical classification and evaluation, it has been concluded that two types of CSR theories, pure and enlighten egoistic CSR, cannot be philosophically preferred. Instead, spiritual-egoistic CSR theories present better contents and programs in comparison with their rivals. Finally, as a suggestion for future investigations, it seems necessary for all CSR theories to both clarify and justify their grounds prior to presenting any other discussions.